The potential anticancer activity of 5-fluorouracil loaded in cellulose fibers isolated from rice straw - Yusefi, Mostafa; Shameli, Kamyar; Jahangirian, Hossein; Teow, Sin Yeang *; Umakoshi, Hiroshi; Saleh, Bahram; Rafiee-Moghaddam, Roshanak; Webster, Thomas (Dove Medical Press, 2020)
Introduction: Green-based materials have been increasingly studied to circumvent off-target cytotoxicity and other side-effects from conventional chemotherapy. Materials and Methods: Here, cellulose fibers (CF) were isolated from rice straw (RS) waste by using an eco-friendly alkali treatment. The CF network served as an anticancer drug carrier for 5-fluorouracil (5-FU). The physicochemical and thermal properties of CF, pure 5-FU drug, and the 5-FU-loaded CF (CF/5-FU) samples were evaluated. The samples were assessed for in vitro cytotoxicity assays using human colorectal cancer (HCT116) and normal (CCD112) cell lines, along with human nasopharyngeal cancer (HONE-1) and normal (NP 460) cell lines after 72-hours of treatment. Results: XRD and FTIR revealed the successful alkali treatment of RS to isolate CF with high purity and crystallinity. Compared to RS, the alkali-treated CF showed an almost fourfold increase in surface area and zeta potential of up to − 33.61 mV. SEM images illustrated the CF network with a rod-shaped structure and comprised of ordered aggregated cellulose. TGA results proved that the thermal stability of 5-FU increased within the drug carrier. Based on UV-spectroscopy measurements for 5-FU loading into CF, drug loading encapsulation efficiency was estimated to be 83 ± 0.8%. The release media at pH 7.4 and pH 1.2 showed a maximum drug release of 79% and 46%, respectively, over 24 hours. In cytotoxicity assays, CF showed almost no damage, while pure 5-FU killed most of the both normal and cancer cells. Impressively, the drug-loaded sample of CF/5-FU at a 250 μg/mL concentration demonstrated a 58% inhibition against colorectal cancer cells, but only a 23% inhibition against normal colorectal cells. Further, a 62.50 μg/mL concentration of CF/5FU eliminated 71% and 39% of nasopharyngeal carcinoma and normal nasopharyngeal cells, respectively. Discussion: This study, therefore, showed the strong potential anticancer activity of the novel CF/5-FU formulations, warranting their further investigation.